Investigating an Unusually Large 28‐Day Oscillation in Mesospheric Temperature Over Antarctica Using Ground‐Based and Satellite Measurements. Issue 15 (10th August 2019) - Zhao, Yucheng; Taylor, M. J.; Pautet, P.‐D.; Moffat‐Griffin, T.; Hervig, M. E.; Murphy, D. J.; French, W. J. R.; Liu, H. L.; Pendleton, W. R.; Russell, J. M.
Abstract: The Utah State University Advanced Mesospheric Temperature Mapper was deployed at the Amundsen‐Scott South Pole Station in 2010 to measure OH temperature at 87 km as part of an international network to study the mesospheric dynamics over Antarctica. During the austral winter of 2014, an unusually large amplitude 28‐day oscillation in mesospheric temperature was observed for 100 days from the South Pole Station. This study investigates the characteristics and global structure of this exceptional planetary‐scale wave event utilizing ground‐based mesospheric OH temperature measurements from two Antarctic stations (South Pole and Rothera) together with satellite temperature measurements from the Microwave Limb Sounder on the Aura satellite and the Solar Occultation For Ice Experiment on the Aeronomy of Ice in the Mesosphere satellite. Our analyses have revealed that this large oscillation is a wintertime, high‐latitude phenomenon, exhibiting a coherent zonal wave #1 structure below 80‐km altitude. At higher altitudes, the wave was confined in longitude between 180°E and 360°E. The amplitude of this oscillation reached 15 K at 85 km, and it was observed to grow with altitude as it extended from the stratosphere into the lower thermosphere in the Southern Hemisphere. The satellite data further established the existence of this oscillation in the Northern Hemisphere during the boreal wintertime. The main characteristics and global structure of this event as observed in temperature are consistent with the predicted 28‐day Rossby Wave (1, 4) mode. Key Points: A large amplitude, persistent 28‐day mesospheric temperature planetary wave event was detected over Antarctica as part of the ANGWIN measurement network A novel combination of ground‐based Antarctic measurements and satellite temperature data was utilized The 28‐day periodicity and the global signatures of this oscillation are similar to the predicted Rossby (1, 4) mode